PURIFICATION AND CHARACTERIZATION OF BIOACTIVE COMPOUND FROM THE METHANOLIC LEAF EXTRACT OF MILLINGTONIA HORTENSIS LINN. - MAHESH KUMAR MVS; VSSL PRASAD TALLURI; S V RAJAGOPAL (International Journal of Pharma and Bio Sciences, 2015)
Millingtonia hortensis is widely distributed tree which belongs to Bignoniaceae family, commonly used as a folk medicine, having anti epileptic, antioxidant, antimicrobial, larvicidal and anticancer activities. In the present study, purification and characterization of bioactive compound(s) from methanolic extract of the leaves of Millingtonia hortensis were carried out using silica gel column chromatography, thin layer chromatography (TLC), high performance liquid chromatography (HPLC), FT-IR and mass spectrometry (LC-MS) detection. Structure of the bioactive compound was determined by nuclear magnetic resonance (13C and 1H NMR) spectroscopy. The S6 fraction obtained from silica gel column chromatography was identified to have potent antioxidant, antimicrobial and antiproliferative activities with a yield of 2090 mg. The Rf value of the isolated bioactive compound was found to be 0.41 using ethylacetate : methanol (9:1) as mobile phase. The molecular weight of the compound was determined using LC-MS was identified as 301 daltons. The FT-IR spectroscopy showed the presence of phenolic hydroxyl, aromatic and methoxy functional groups. The purified compound was identified as 5,7-dihydroxy-2-(4-hydroxyphenyl)-6-methoxy-4H-chromen-4-one (Hispidulin) by NMR spectroscopy. The isolated pure bioactive compound was named as MHH.